Strengthening Students' Religious Character through Extracurricular Activities at Muhammadiyah Elementary School - Renata Kartikasari; Muhlasin Amrullah; Khizanatul Hikmah (research, training and philanthropy institution Natural Aceh, 2023)
This research aims to determine the implementation, supporting factors, and inhibiting factors of strengthening religious character in the extracurricular activities of Da'i Cilik and BTQ. The research conducted is qualitative research with a phenomenological approach. The subjects of this research are the school principal and extracurricular coaches. The data collection techniques used include interviews, observation, and documentation. The researcher serves as the instrument in this research. The data analysis techniques used include data reduction, data presentation, and conclusion drawing. The data validity is tested through triangulation of sources and techniques. The results of this research show the implementation of strengthening religious character education through the extracurricular activities of Da'i Cilik and BTQ. This includes strengthening religious character through exemplary activities such as habituation, preaching material, praise and advice, and assessment. The supporting factors for strengthening religious character include the availability of facilities and infrastructure, student attendance and seriousness, and parental support. The inhibiting factors include students' lack of self-confidence and the absence of props. The impact of strengthening religious character on students is evident in increased awareness and obligations as Muslims, increased diligence in performing prayer and reading the Qur'an, improved polite and respectful attitudes among students, enhanced self-confidence, independence, and discipline in daily activities in accordance with Islamic teachings.